Network of remote and local protein dynamics in dihydrofolate reductase catalysis - Singh, Priyanka (ACS Catal, 2015)
Molecular dynamics calculations and bionformatic studies of dihydrofolate reductase (DHFR) have suggested a network of coupled motions across the whole protein that is correlated to the reaction coordinate. Experimental studies demonstrated that distal residues G121, M42 and F125 in E. coli DHFR participate in that network. The missing link in our understanding of DHFR catalysis is the lack of a mechanism by which such remote residues can affect the catalyzed chemistry at the active site. Here, we present a study of the temperature dependence of intrinsic kinetic isotope effects (KIEs) that indicates synergism between a remote residue in that dynamic network, G121, and the active site’s residue I14. The intrinsic KIEs for the I14A-G121V double mutant showed steeper temperature dependence (ΔE(a(T-H))) than expected from comparison of the wild type and two single mutants. That effect was non-additive, i.e., ΔE(a(T-H)G121V) +ΔE(a(T-H) I14A) < ΔE(a(T-H) double mutant), which indicates a synergism between the two residues. This finding links the remote residues in the network under investigation to the enzyme’s active site, providing a mechanism by which these residues can be coupled to the catalyzed chemistry. This experimental evidence validates calculations proposing that both remote and active site residues constitute a network of coupled promoting motions correlated to the bond activation step (C-H→C hydride transfer in this case). Additionally, the effect of I14A and G121V mutations on single turnover rates was additive rather than synergistic. Although single turnover rate measurements are more readily available and thus more popular than assessing intrinsic kinetic isotope effects, the current finding demonstrates that for these rates, which in DHFR reflect several microscopic rate constants, can fall short of revealing the nature of the C-H bond activation per se.